De educación social - Hoz, Víctor Garccía (Revista Española de Pedagogía, 2025)
In this article Dr. García Hoz means, in a purely informative way, to answer the question: "how are those educators formed who are neither teachers nor parents considedered as such educators?" In order to facilitate the understanding of this problem he centers his study in three different aspects, politic, religious and undifferentiated one. The author poses the problem of the relationship between education and politics' and points out the politic concern on educational questions. He explains the service which education renders to politics and shows the inter-action of both of them in Spain. He studies the double aspect of the religious and educational problem to show its influence on pedagogical method and on the catechistical societies and on the National Catholic Action. After explaining the existing link betwen the above mentioned fields and the undifferentiated social one he gives a complete account of the Spanish societies whose specific aims and characteristics are social. He ends by stating the utility of these formative types and the convenience of increasing their contact with the professional educational institutions.